Proinflammatory cytokines and matrix metalloproteinases in CSF of patients with VZV vasculopathy. Issue 4 (August 2016) - Jones, Dallas; Alvarez, Enrique; Selva, Sean; Gilden, Don; Nagel, Maria A.
Abstract : Objective: To determine the levels of proinflammatory cytokines and matrix metalloproteinases (MMPs) in the CSF of patients with virologically verified varicella zoster virus (VZV) vasculopathy. Methods: CSF from 30 patients with virologically verified VZV vasculopathy was analyzed for levels of proinflammatory cytokines and MMPs using the Meso Scale Discovery multiplex ELISA platform. Positive CNS inflammatory disease controls were provided by CSF from 30 patients with multiple sclerosis. Negative controls were provided by CSF from 20 healthy controls. Results: Compared to multiple sclerosis CSF and CSF from healthy controls, levels of interleukin (IL)-8, IL-6, and MMP-2 were significantly elevated in VZV vasculopathy CSF. Conclusions: CSF of patients with VZV vasculopathy revealed a unique profile of elevated proinflammatory cytokines, IL-8 and IL-6, along with elevated MMP-2. The relevance of these cytokines to the pathogenesis of VZV vasculopathy requires further study.